BAY 1143269, a novel MNK1 inhibitor, targets oncogenic protein expression and shows potent anti-tumor activity. (1st April 2017) - Santag, Susann; Siegel, Franziska; Wengner, Antje M.; Lange, Claudia; Bömer, Ulf; Eis, Knut; Pühler, Florian; Lienau, Philip; Bergemann, Linda; Michels, Martin; von Nussbaum, Franz; Mumberg, Dominik; et al.
Abstract: The initiation of mRNA translation has received increasing attention as an attractive target for cancer treatment in the recent years. The oncogenic eukaryotic translation initiation factor 4E (eIF4E) is the major substrate of MAP kinase-interacting kinase 1 (MNK1), and it is located at the junction of the cancer-associated PI3K and MAPK pathways. The fact that MNK1 is linked to cell transformation and tumorigenesis renders the kinase a promising target for cancer therapy. We identified a novel small molecule MNK1 inhibitor, BAY 1143269, by high-throughput screening and lead optimization. In kinase assays, BAY 1143269 showed potent and selective inhibition of MNK1. By targeting MNK1 activity, BAY 1143269 strongly regulated downstream factors involved in cell cycle regulation, apoptosis, immune response and epithelial–mesenchymal transition in vitro or in vivo . In addition, BAY 1143269 demonstrated strong efficacy in monotherapy in cell line and patient-derived non-small cell lung cancer xenograft models as well as delayed tumor regrowth in combination treatment with standard of care chemotherapeutics. In summary, the inhibition of MNK1 activity with a highly potent and selective inhibitor BAY 1143269 may provide an innovative approach for anti-cancer therapy. Highlights: BAY 1143269 is a novel, potent and selective small molecule inhibitor of MNK1. BAY 1143269 strongly reduced oncogenic MNK1 substrate phospho-eIF4E. MNK1 downstream targets involved in tumorigenesis were downregulated by BAY 1143269. In vivo, BAY 1143269 monotherapy showed significant efficacy in xenograft models. Chemo-combination therapy with BAY 1143269 delayed tumor regrowth in vivo .